A central role for hepatic conventional dendritic cells in supporting Th2 responses during helminth infection. Issue 4 (12th January 2016) - Lundie, Rachel J; Webb, Lauren M; Marley, Angela K; Phythian‐Adams, Alexander T; Cook, Peter C; Jackson‐Jones, Lucy H; Brown, Sheila; Maizels, Rick M; Boon, Louis; O'Keeffe, Meredith; MacDonald, Andrew S
Abstract : Dendritic cells (DCs) are the key initiators of T‐helper (Th) 2 immune responses against the parasitic helminth Schistosoma mansoni . Although the liver is one of the main sites of antigen deposition during infection with this parasite, it is not yet clear how distinct DC subtypes in this tissue respond to S. mansoni antigens in vivo, or how the liver microenvironment might influence DC function during establishment of the Th2 response. In this study, we show that hepatic DC subsets undergo distinct activation processes in vivo following murine infection with S. mansoni . Conventional DCs (cDCs) from schistosome‐infected mice upregulated expression of the costimulatory molecule CD40 and were capable of priming naive CD4 + T cells, whereas plasmacytoid DCs (pDCs) upregulated expression of MHC class II, CD86 and CD40 but were unable to support the expansion of either naive or effector/memory CD4 + T cells. Importantly, in vivo depletion of pDCs revealed that this subset was dispensable for either maintenance or regulation of the hepatic Th2 effector response during acute S. mansoni infection. Our data provides strong evidence that S. mansoni infection favors the establishment of an immunogenic, rather than tolerogenic, liver microenvironment that conditions cDCs to initiate and maintain Th2 immunity in the context of ongoing antigen exposure.